Сучасні моделі соціальної держави - Сковронський, Д. М. (Видавництво Львівської політехніки, 2016)
Сучасний тип ринкового господарювання вимагає сучасних ідей побудови соціальної держави. Саме тому міжнародне співтовариство визначило пріоритетні напрямки, які полягають у політичному та правовому упорядкуванні життя суспільства на засадах гуманізму, виконанні державою комплексу соціально-захисних функцій, створенні умов для розвитку громадянського суспільства. Після Другої світової війни в країнах з ринковою економікою склалися різні моделі соціальних держав і, відповідно, різні механізми реалізації соціальної політики. Зокрема, виділяють ліберальну, корпоративну та суспільну (солідарну) моделі. Вони відрізняються одна від одної роллю та ступенем участі в реалізації соціальної політики, насамперед трьох її основних суб’єктів – держави, корпорації осіб, та інших інститутів громадянського суспільства. В основі кожної з моделей соціальної держави свій основоположний принцип, що випливає зі співвідношення відсотків участі в реалізації соціальної політики її основних суб’єктів. Современный тип рыночного хозяйствования требует современных идей построения социального государства. Именно поэтому международное сообщество определило приоритетные направления, которые заключаются в политической и правовой составляющей жизни общества на принципах гуманизма, выполнении государством комплекса социально-защитных функций, создании условий для развития гражданского общества. После Второй мировой войны в странах с рыночной экономикой сложились разные модели социальных государств и, соответственно, разные механизмы реализации социальной политики. В частности, выделяют либеральную, корпоративную и общественную (солидарную) модели. Они отличаются друг от друга ролью и степенью участия в реализации социальной политики, прежде всего трех ее основных субъектов – государства, корпорации лиц и других институтов гражданского общества. В основе каждой из моделей социального государства имеется свой основополагающий принцип, вытекающий из соотношения процентов участия в реализации социальной политики ее основных субъектов. The current type of market economy requires modern ideas of building a welfare state. That is why the international community has identified priority areas, which are the political and legal ordering of society on the principles of humanism, of a government complex social and protective functions, creating conditions for the development of civil society. After the World War II in emerging economies have developed different models of welfare states and therefore different mechanisms of realization of social policy. In particular, isolated liberal, corporate and public (PAYG) model. They differ role and degree of participation in the implementation of social policy, especially its three main actors – government, corporate entities, and other institutions of civil society. At the heart of each model social state a fundamental principle, derived from the ratio of interest participation in the social policies of its main actors. Continuous development of state and society give rise to new forms of simultaneous transformation or demise is already available. For example, some researchers call the future model of the welfare state "state of social democracy". It has become the organization of political power of owners in which really ensured maximum realization and protection of the rights and fundamental freedoms, the rights of the nation and the people, the exercise of power on universal principles of freedom, justice and solidarity.
Современные модели социального государства
Current state of social model
Keywords: соціальна держава; соціально-захисні функції; соціальна політика; модель соціальної держави; социальное государство; социально-защитные функции; соци- альная политика; модель социального государства; welfare state; social and protective functions; social policy; welfare state model